Reducing Vulnerability to Depression: A Route of Vitamins - Gupta, Dr. Sunil; Thakur, Dr. Satyendra Kumar; Srivastav, Dr. Deepika; Dwivedi, Dr. Tosendra (South Eastern European Journal of Public Health, 2024)
This study investigates how vitamin D can lessen a person's vulnerability to depression. Given that depression is one of the most common mental health conditions in the world, it is crucial to comprehend potential preventive factors. According to recent studies, vitamin D may be important for mood management and cognitive performance since it affects the neurotransmitter systems in the brain. The relationship between vitamin D levels and depression proneness is reviewed in this paper, along with the possibility that vitamin D supplementation could lessen depressed symptoms or the chance of developing depression. The results demonstrate vitamin D's potential as an affordable, supplementary method in depression prevention techniques. But more carefully monitored researches are needed to determine optimal dosage and the precise mechanisms involved.